From Poison to Medicine: Self-Forgiveness as Liberation in Jewish Faith-Based Therapeutic Communities for Addiction Recovery in Israel - Ben-Yair, Yitzhak (Journal of religion and health, 2026)
This qualitative study explores the experiences of individuals participating in forgiveness therapy within a Jewish faith-based therapeutic community for addiction recovery. Using a phenomenological approach, we conducted in-depth interviews with 12 male participants who completed a theologically and culturally adapted forgiveness therapy intervention. The intervention integrated practical applications of Jewish spiritual teachings into Enright's forgiveness therapy model and was delivered over 12 weekly sessions at Israel's largest Jewish residential therapeutic community. Thematic analysis revealed four key themes: the struggle to forgive others, self-forgiveness as the central pathway to healing, emotional control and empowerment, and group support within the therapeutic community. Self-forgiveness emerged as the primary catalyst for recovery, while the gradual nature of forgiveness required sustained engagement. This therapeutic approach enhanced participants' sense of connection through meaning-making within the group. The study illustrates the practical application of forgiveness therapy in a faith-based context, highlighting self-forgiveness along with group and community support as critical elements of the recovery process.